The Influence of Training & Development and Transformational Leadership on Job Performance: Mediated by Job Satisfaction of Banking Employees - Pentury, Luther Aprinando; Tanuwijaya, Justine; Gunawan, Andreas Wahyu (Jurnal Economic Resource, 2024)
The purpose of this study was to analysed and discuss the positive and significant influence between Training and Development and Transformational Leadership on Job Performance and Job Satisfaction in Banking Employees. The research method used is Quantitative research. The data collection techniques used are through observation activities, interviews with several sources, and questioner distribution activities distributed via google form. The data analysis used is descriptive statistics, Structural Equation Modelling (SEM) approach and Smart PLS analysis. The results showed that there was an influence between the independent variables (transformational leadership, training and development, job satisfaction) on the dependent variable (Job Performance). The conclusion of the research is that this research contradicts previous research which explains that the training and development strategy carried out can improve Job Performance. This research is limited to the variables of Job Performance, Training & Development, Job Satisfaction, and Transformational Leadership, with the object of research in banking companies.